A Bi-National Appellation of Origin: Pisco in Chile and Peru - Lacoste, P (Instituto de Investigaciones Agropecuarias, INIA, 2013)
Pisco is a brandy made from selected grapes, restricted as Appellation of Origin (AO) in 1931 in Chile by executive order number 181 of May 15, and also legally protected by Peru in 1991 by executive resolution of December 12 and executive order 001-91-ICTI/IND of January 16. This AO has given rise to a commercial controversy between producers of both countries, who claim it as their own. This article proposes a new thesis: The AO of pisco is actually bi-national, belonging to Chile as well as to Peru. The reason is that the producers of the two countries contributed to the origin and consolidation of this product. Pisco would not exist without the participation of both of them. Therefore, the two countries have coownership rights since they are co-founders.